Peningkatan Kapasitas Pengurus Organisasi: Menguatkan Sinergi, Menyalakan Inovasi dan Menggapai Prestasi - Miran, Ikas; Chandra, Stefani; Suyono, Suyono; Kudri, Wan Muhamad; Hocky, Agus; Estu, Ahmad Zulkarnaen; Hadi, Syukri; Novitriansyah, Bob (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
The Department Student Association has an important role in developing leadership, managerial skills and synergy between members. However, various challenges such as weak coordination, lack of strategic planning, and lack of innovation often hinder the achievement of organizational goals. This community service program aims to increase the capacity of student organization administrators through a series of training. The approach used includes training on organizational governance, effective communication, and the use of digital technology in administration. With this method, it is hoped that administrators can increase their competence in managing the organization in a more professional, effective and innovative manner. The results of this program show an increase in management's understanding and skills in various aspects of organizational leadership and management. In addition, synergy between organizational members is getting stronger, enabling the creation of a more productive and collaborative work environment. This program is expected to have a long-term impact on the desires and achievements of student organizations, as well as building an organizational culture that is more adaptive and highly competitive in the academic environment and wider society. Himpunan Mahasiswa Jurusan memiliki peran penting dalam mengembangkan kepemimpinan, keterampilan manajerial, serta sinergi antaranggota. Namun, berbagai tantangan seperti lemahnya koordinasi, kurangnya perencanaan strategis, serta minimnya inovasi seringkali menghambat pencapaian tujuan organisasi. Program pengabdian masyarakat ini bertujuan untuk meningkatkan kapasitas pengurus organisasi mahasiswa melalui serangkaian pelatihan. Pendekatan yang digunakan meliputi pelatihan tentang tata kelola organisasi, komunikasi efektif, serta sejarah Himpunan dari masa ke masa. Dengan metode ini, diharapkan para pengurus dapat meningkatkan kompetensi dalam mengelola organisasi secara lebih profesional, efektif, dan inovatif. Hasil dari program ini menunjukkan peningkatan pemahaman dan keterampilan pengurus dalam berbagai aspek kepemimpinan dan manajemen organisasi. Selain itu, sinergi antaranggota organisasi semakin kuat, memungkinkan terciptanya lingkungan kerja yang lebih produktif dan kolaboratif. Program ini diharapkan dapat memberikan dampak jangka panjang terhadap keberlanjutan dan prestasi organisasi mahasiswa, serta membangun budaya organisasi yang lebih adaptif dan berdaya saing tinggi di lingkungan akademik maupun masyarakat luas.